Azoximer Bromide: Mystery, Serendipity, and Promise - Grivtsova, Lyudmila Yuryevna; Falaleeva, Natalia Alexandrovna; Tupitsyn, Nikolay Nikolaevich (Frontiers in Oncology, 2021)
Azoximer bromide (AZB) was identified as an immunomodulator, and was initially developed and currently successfully indicated as one of several natural polyelectrolytes, a vaccine adjuvant, and an effective agent for the treatment of infectious and inflammatory diseases of viral, bacterial, and fungal origin. Azoximer bromide has the potential to increase an individual’s resistance to local and general infection and is indicated for the treatment of viral infections, and has also demonstrated clinical efficacy in the treatment of a variety of secondary immunodeficiencies. However, AZB does offer long-term promise beyond infection conditions. Multiple clinical trials and research studies in cancer patients, reported the use of AZB with a favourable safety profile, raising the possibility that it may have direct antitumor properties as a promising anticancer agent for use as monotherapy or by supporting complex/combination therapy. This literature review aims to analyse the novel mechanisms that mediate the AZB direct anticancer effects. All the clinical observations and studies explored in this review show favourable tolerability and high safety of AZB in cancer patients, along with significant carcinoma growth delay, reduce the frequency of metastasis, lowering the number of infectious complications during chemotherapy, and significantly increase in overall patient survival rate. Thus, AZB appears to show all the signs of an agent that could support existing therapeutic regimens at different treatment stages in cancer patients. Consequently, azoximer bromide should be considered as a promising anticancer agent of choice for various cancer types, and use both as part of complex/combination therapy, as well as, monotherapy.